Pharmacokinetic and pharmacodynamic properties of pantoprazole in calves - Olivarez, Jeff D.; Mulon, Pierre-Yves; Ebner, Lisa S.; Cremerius, Haley; Cantrell, Channing; Rahn, Rebecca; Soto-Gonzalez, Windy; Bergman, Joan; Cox, Sherry; Mochel, Jonathan P.; Kreuder, Amanda J.; Smith, Joe S. (Frontiers in Veterinary Science, 2023)
Introduction Development of abomasal ulceration is a large concern, especially within calves; however, there is a paucity of research into the use of gastro protectants in ruminant species. Proton pump inhibitors, such as pantoprazole, are widely used in humans and companion animals. Their efficacy in ruminant species is undetermined. The objectives of this study were to 1) estimate the plasma pharmacokinetic parameters for pantoprazole in neonatal calves after three days of intravenous (IV) or subcutaneous (SC) administration, and 2) measure the effect pantoprazole had on abomasal pH over the treatment period. Methods Pantoprazole was administered to 6 Holstein-Angus cross bull calves at a dose of 1 mg/kg (IV) or 2 mg/kg (SC), once a day (every 24 h) for three days. Plasma samples were collected over a 72 h period and analyzed via HPLC-UV for determining pantoprazole concentrations. Pharmacokinetic parameters were derived via non-compartmental analysis. Abomasal (n= 8) samples were collected via abomasal cannulas over a 12 h period, per calf per day. Abomasal pH was determined via a bench top pH analyzer. Results Following Day 1 of IV administration, plasma clearance, elimination half-life, and volume of distribution of pantoprazole were estimated at 199.9 mL/kg/h, 1.44 h, and 0.51 L/kg, respectively. On Day 3 of IV administration, the reported values were 192.9 mL/kg/h, 2.52 h, and 1.80 L/kg mL, respectively. Elimination half-life and volume of distribution (V/F) of pantoprazole following SC administration were estimated at 1.81 h and 0.55 L/kg, respectively, on Day 1; and 2.99 h and 2.82 L/kg, respectively, on Day 3. Discussion The reported values for IV administration were similar to those previously reported in calves. SC administration appears to be well absorbed and tolerated. The sulfone metabolite was detectable for 36 h after the last administration for both routes. Abomasal pH was significantly higher than the pre-pantoprazole pH 4, 6, and 8 h after administration in both the IV and SC groups. Further studies of pantoprazole as a treatment/preventative for abomasal ulcers are warranted.